ANALISIS MODEL PENYUSUNAN FORMASI DAN PROSES PENGADAAN PEGAWAI NEGERI SIPIL : (Studi pada Pemerintah Kabupaten Lamongan) - Ainun Najib, M. Firdam (Jurnal Administrasi Publik, 2024)
Analysis of the Formation Model and Procurement Process for Civil Servants (Study in the Lamongan Regency Government). Preparing the formation and procurement of civil servants is important in human resource management in the public sector. Lamongan Regency carried out this process to meet the needs of the 49% shortage of employees. Success in fulfilling this cannot be separated from the models and processes that are interesting to study in this research. This research uses a descriptive-qualitative perspective which aims to understand the process of preparing formation and procurement of employees at BKPSDM Lamongan Regency which will be explained based on relevant theories. The method used is a case study to examine 3 (three) main aspects, namely the model aspect in planning human resources, recruitment and the employee procurement process. This study aims to describe the process of preparing the formation and procurement of employees in the Lamongan Regency Government. There are 3 (three) findings in this research, the first is the planning aspect that uses collaboration. Second, the recruitment and selection aspect describes a process based on a successful hurdles selection approach. Third, procurement is still stopped at the fifth stage of the 7 (seven) stages of civil servant procurement..